Healthy Business? Managerial Education and Management in Health Care - Bloom, Nicholas; Lemos, Renata; Sadun, Raffaella; Van Reenen, John (The Review of Economics and Statistics, 2020)
We investigate the link between hospital performance and managerial education by collecting a large database of management practices and skills in hospitals across nine countries. We find that hospitals closer to universities offering both medical education and business education have lower mortality rates from acute myocardial infarction (heart attacks), better management practices, and more MBA-trained managers. This is true compared to the distance to universities that offer only business or medical education (or neither). We argue that supplying bundled medical and business education may be a channel through which universities improve management practices in hospitals and raise clinical performance.